Circadian preference and decision-making styles. Issue 4 (3rd July 2016) - Tonetti, Lorenzo; Fabbri, Marco; Boreggiani, Michele; Guastella, Pietro; Martoni, Monica; Ruiz Herrera, Noelia; Natale, Vincenzo
Abstract: The present study aimed to explore for the first time the relationship between circadian preference and different decision-making styles. In total, 501 young adults (330 females), with a mean age of 21.07 ± 1.99 years, took part in the study. The participants completed the reduced version of the morningness–eveningness questionnaire (rMEQ) and the general decision-making style inventory (GDMS). The rMEQ enabled to assess the circadian preference, with lower rMEQ scores pointing toward eveningness preference. The GDMS measured five decision-making styles: rational, intuitive, dependent, avoidant and spontaneous. Higher scores on each GDMS decision-making style reflect a higher prevalence of the corresponding style. A set of multiple regression analyses was performed with rMEQ score, gender and age as predictors together with each GDMS decision-making style as dependent variable. rMEQ score proved to be the only significant (negative) predictor of avoidant and spontaneous decision-making styles, i.e. lower rMEQ score (tendency toward eveningness) significantly predicted higher score at these decision-making styles. The present results suggest that eveningness preference is significantly related to avoidant and spontaneous decision-making styles in young adults. Such results will be discussed with reference to the effects of decision-making styles on decision-making in different types of workers and mental health.